BURMAâS ROHINGYA CASE IN INTERNATIONAL LAW PERSPECTIVE - Gunawan, Yordan; Priambodo, Gatot (Jurnal Media Hukum, 2013)
Nowadays, the refugees issue is becoming serious problem to the international community. The problems of refugees becomes increase day by day along with a man-made disaster or a nature disaster. The Rohingyas ethnic is one of examples for refugee who caused by man-made disaster. They, the Rohingyas, experienced a persecution done by the military junta of Myanmar, their own government. The government of Myanmar doesnât recognized that the Rohingyas belong to the citizen of Myanmar. With this condition, the Rohingyas called as a stateless person. They have no citizenship status. So they have no protection from any countries because they are stateless. The persecution from the Myanmarâs government make them, the Rohingyas, fled to another countries to get an asylum. Sometimes the presence of refugees in the country of transit or destination countries were forcibly repatriated . Such treatment is clearly contrary to the principles of international law recognized by civilized nations.There are some regulations pertaining to the issue of refugees, which are guarantee the rights of refugee. The right to get an asylum as stated in Article 14 (1) Universal Declaration of Human Rights. But the fact, there are many violations in refugees treatment done by some countries. The study is normative legal research with Statute Approach and Case Approach. This study would analysis the Rohingyas asylum-seeker based on some international laws concerning this problem as for the 1951 Convention Relating to the Status of Refugees and its protocol. The result shows the international law relating to the refugees issu that applicable to the Rohingyas case.Keywords: